2012
DOI: 10.1002/eji.201141933
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17 neutralization significantly ameliorates hepatic granulomatous inflammation and liver damage in Schistosoma japonicum infected mice

Abstract: IL-17 is a signature cytokine of Th17 cells implicated in the induction and progression of chronic inflammatory diseases. Several studies in C57BL/6 mice, immunized with soluble schistosome egg Ags (SEA) in complete Freund's adjuvant (CFA), and subsequently infected with Schistosoma mansoni (S. mansoni) have shown that severe hepatic granulomatous inflammation is correlated with high levels of IL-17. Here, using a Schistosoma japonicum (S. japonicum) larvae infection model in C57BL/6 mice, we analyzed the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 64 publications
3
75
0
Order By: Relevance
“…Expression of egr1 in the liver was suppressed midway through the TCE exposure, but then rebounded at the final 40-week time point. Increased levels of pro-inflammatory cytokines/chemokines such as TNF-α, osteopontin, serum amyloid A (SAA) and CXCL1 have been implicated in the induction or progression of chronic liver inflammation (Iwamoto et al , 2013; Nagoshi, 2014; Gollaher et al , 1990; Zhang et al , 2012). Hepatic expression of these Saa2 , Cxcl1 and Spp1 (encodes for osteopontin) were for the most part unchanged or decreased during all but the last 40-week time point of TCE exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of egr1 in the liver was suppressed midway through the TCE exposure, but then rebounded at the final 40-week time point. Increased levels of pro-inflammatory cytokines/chemokines such as TNF-α, osteopontin, serum amyloid A (SAA) and CXCL1 have been implicated in the induction or progression of chronic liver inflammation (Iwamoto et al , 2013; Nagoshi, 2014; Gollaher et al , 1990; Zhang et al , 2012). Hepatic expression of these Saa2 , Cxcl1 and Spp1 (encodes for osteopontin) were for the most part unchanged or decreased during all but the last 40-week time point of TCE exposure.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Kang et al 110 reported that EA enhances production IgG subclass (IgG2a, IgG2b and IgG3). It has been shown that administration of anti-IL-17 neutralizing mAb significantly increased SEA-specific IgG, but the other antibodies did not change significantly 95,111 . Herein, we demonstrated that EA treatment decreased IL-17 production.…”
Section: Discussionmentioning
confidence: 98%
“…35,36 Moreover, lower expression of IL-6 and IL-1β (pro-inflammatory cytokines) causes a down-modulation of granulomatous inflammation and hepatocyte necrosis. 37 Also, macrophages could be activated to produce NO and other inflammatory mediators by IFN-γ, which is considered as an important inducer of iNOS. In addition, Abdallahi et al 38 detected iNOS mRNA in the liver at the onset of parasite egg laying; the authors showed that the levels then increased as the eggs accumulated in the liver.…”
Section: Discussionmentioning
confidence: 99%